Electrophysiological variations of Guillain-Barre syndrome in Bangladesh- Hospital based study (Journal of Medicine, 2024)
Introduction: Guillain-Barre syndrome (GBS) is an immune mediated disorder of peripheral nerves which usually presents by rapidly evolving ascending weakness & mild sensory loss and hypo- or areflexia. Electrodiagnostic study (EDS) is the basis for classification of different subtypes of the disease. EDS also has a crucial role in diagnosis, ruling out of some differential diagnosis like myopathic and motor neuron disorders and confirming the neuropathic nature of GBS. The benefit of immunotherapy is greatest when introduced early. In addition, electrophysiological characteristic can predict the prognosis of patients with GBS. This study was conducted to determine the predominant subtype and electrophysiological pattern of GBS in the context of Bangladesh.Objectives: Objective of this study was to compare the electrophysiological variations among different electrophysiological subtypes of GBS.Methods: It is an observational cross sectional study conducted in Department of Medicine and Neurology, Sir Salimullah Medical College & Mitford Hospital and National Institute of Neuroscience (NINS), Dhaka, over a period of one year & four months. Total 30 patients were selected by purposive sampling technique. Demographic data were collected from the patients and recorded in structured case report form. Clinical examination and relevant investigations were done meticulously. Collected questionnaire were checked to identify any error in data. Data was analyzed with SPSS version 21 software.Result: In this study, maximum numbers of patients 53% were between 21-30 years of age group with mean value 27.47±8.1 years. Male to female ratio was 1.7:1. Frequency of Guillain-Barre syndrome is predominance at middle age group. Commonest presentation was limb weakness (parapledgia or quadripledgia) in 60% patients, paresthesias & numbness (40%), pain (100%) and deviation of mouth (63%) of GBS patients. Cerebrospinal fluid shows a mild pleocytosis (5 to 50 cells/µl) in majority of cases was found in 76%  of patients. Whereas elevated CSF Protein (>45 mg/dl) was seen in all GBS patient. Increased distal motor latency (DML) was found in 93% patients, whereas 7% patients had normal DML. In the case of the lower limbs, increased distal motor latency was predominant. Decreased amplitude of sensory nerve action potential (SNAP) was seen in 83% patients while 16% patients had normal. Slowing of motor conduction velocities, decreased amplitude as well as increase in distal motor latencies were observed, being more pronounced in the lower limbs. F-wave was completely absent in 20.0% patients while 20% patients showed decreased conduction velocity with prolonged latency. Sensory nerve action potential revealed that decreased  sensory  conduction  velocity  (SCV)  was  seen  in  26%,  absent  SCV  in  10%  and  normal  SCV  in  63% patients. Present study demonstrated that Acute inflammatory demyelinating polyneuropathy (AIDP) was the commonest type of Guillain-Barré syndrome, present in 56% of patient. Around 30% of the patients belonged to acute motor axonal polyneuropathy (AMAN) and 13% were acute motor sensory axonal polyneuropathy (AMSAN).Conclusion: In this study AIDP was the most frequent subtype. The characteristic findings supportive of AIDP include prolonged distal motor latencies, reduced conduction velocities, conduction blocks at non-entrapment sites, temporal dispersion and prolonged F wave latencies.J MEDICINE 2024; 25: 11-16